Feminism in Abidah El Khalieqy’s Novel Perempuan Berkalung Sorban - Sipahutar, C H (KnE Social Sciences, 2018)
The problem in this research shows feminism in the novel entitled Perempuan Berkalung Sorban by Abidah El Khalieqy. Therefore, the purposes of this research are to reveal feminism reflected in Perempuan Berkalung Sorban, and to describe the kinds of feminism found in the novel. This research employs descriptive qualitative research proposed by Lambert (2009). The theory of feminism applied in this research is following Rose (2003) in which she claims that feminism views the differences in gender role of men and women, and in general feminism can be categorized into two groups namely liberal feminism and radical feminism.Based on the research of the data in Perempuan Berkalung Sorban, the results show that the feminism in Perempuan Berkalung Sorban describes the struggle of a woman by the name of Annisa in getting her existences and rights as an independent human being in life, and contains Liberal Feminism and Radical Feminism. Keywords: feminism, fiberal feminism, radical feminism.